Activity-based cost analysis of opioid-related nausea and vomiting among inpatients - Eberhart, MD, Leopold; Koch, MSc, Tilo; Kranke, MD, Peter; Rüsch, MD, Dirk; Torossian, MD, Alexander; Nardi-Hiebl, MBA, Stefan (Journal of Opioid Management, 2014)
Objective: Nausea and/or vomiting (N/V) are frequent side effects of opioid drugs. These are of major concerns to patients and caregivers and only few studies have focused on their economical costs. Design: This is a prospective, nonproduct-related, activity-based evaluation of personnel and material costs of opioid-related N/V among inpatients. Setting: Data were obtained from surgical, general medicine, and palliative care wards at 16 German hospitals of different size, healthcare mandate, and ownership. Patients, participants: According to predefined criteria, of 462 documented N/V events, 340 were diagnosed as opioid related. Interventions: Elicited activities and pharmacological interventions for N/V episodes followed local standards. Main outcome measure: Both materials used and the time engaged to treat patients with N/V were documented on an “ad hoc” activity recording form. The total cost of an opioid-related N/V episode was calculated based on standard wages of the involved personnel and standard costs of the inherent materials used. Results: Mean staff tenure time for handling an episode of N/V was 26.2 ± 19.8 minutes (nausea 16.9 ± 28.7 minutes; nausea + vomiting: 33.4 ± 26.8 minutes). In the German context, this corresponds to average personnel costs of €18.06 ± 13.64. Material cost contributes to another €13.49 ± 13.38 of costs mainly depending on acquisition costs of antiemetic drugs. Conclusions: N/V showed to have impact on workload of nurses and (to lesser extent) physicians and economic burden of €31 ± 22 for each N/V episode. In view of these results, the potential costs of strategies to minimize the incidence of N/V (use of antiemetics and/or the use of new analgesics) should be outweighed against the incurred costs of N/V.